Analysis of negotiation episodes in foreign language learner interactions - Hazleena Baharun,; Haliza Harun,; Juliana Othman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In second/foreign language learning, it is hypothesised oral interaction facilitates language acquisition. Studies show that one aspect of interaction that promotes second/foreign language acquisition is through the process of negotiation, and one factor that influences interaction is the task or activity that learners are engaged in. Hence, it is the aim of this study to investigate if foreign language (FL) learners would engage in different negotiation strategies when completing different communication task types. Nine FL learners from a tertiary EFL class in groups of three participated in the study. They completed three different communication task types (i.e., information gap, jigsaw and decision-making) over a period of four weeks. Data for the study comprised transcribed recordings of the groups’ oral interaction. This study qualitatively examined FL learners’ oral interactions when engaged in three different types communication tasks. Data collected were analysed for instances of negotiation. Findings revealed that the different communication tasks elicited negotiation episodes as the participants engaged in task completion. They applied similar negotiation strategies during peer interaction. However, further scrutiny revealed that there were differences in terms of the depth of negotiation for the different communication task types. The results of this study exhibit evidence that language communication tasks do promote meaningful interactions among tertiary EFL learners. Data clearly showed widespread negotiation episodes during task completion. The knowledge on the types of communication tasks that can promote meaningful interaction and negotiation episodes can assist language practitioners to make informed decisions on tasks that are suitable for their learners.